Nematode Diversity in Oilseed Crops from Malwa Region of Punjab, India (Indian Journal of Nematology, 2024)
Roots and soil were sampled during 2009-2012 from various localities in 9 districts for the presence of plant parasitic nematodes in Malwa region of Punjab, India. The oilseed crops such as sunflower (Helianthus annuus L.), cotton (Gossypium hirsutum L.), mustard & rapeseed (Brassica compastris L.) and groundnut (Arachis hypogaea L.) were extensively surveyed. The genera recorded were Hoplolaimus spp., Helicotylenchus spp., Rotylenchus sp., Hirschmanniella spp., Pratylenchus spp., Mesocriconema spp., Hemicriconemoides sp., Tylenchorhynchus spp., Telotylenchoides sp., Quinisulcius sp., Meloidogyne sp., Filenchus sp., Psilenchus sp., Aphelenchus sp., Aphelenchoides sp., Xiphinema spp. and Longidorus spp. A total number of 34 species were studied, out of these three viz. Quinisulcius indicus, Psilenchus iranicus and Aphelenchoides parietinus were detected for the first time from sunflower, mustard and rapeseed crops in Malwa region of Punjab, India. The most frequently encountered were Hoplolaimus spp. (62.36%) in soil and root samples of various oilseed crops, followed by Helicotylenchus spp. (57.36%) and Hirschmanniella spp. (24.65%). Large population (1200-5080 J2 per 200 cc of soil) of second stage juveniles of Meloidogyne incognita from Fatehgarh Sahib were observed in sunflower crop. The sunflower plants in the field did not showed any external above ground symptoms. Whereas the lance nematode, Hoplolaimus spp. was encountered in all the oilseed crops with population (20-2040 adults per 200 cc of soil). Free-living nematodes including rhabditids, dorylaimids and mononchids were also found in soil samples.